Biomechanical Analysis of Simulated Clinical Testing and Reconstruction of the Anterolateral Ligament of the Knee. (September 2015) - Spencer, Luke; Burkhart, Timothy A.; Tran, Michael N.; Rezansoff, Alex James; Deo, Shaneel; Caterine, Scott; Getgood, Alan M.
Background: Anatomic anterolateral ligament (ALL) reconstruction has been proposed to assist anterior cruciate ligament (ACL) reconstruction in controlling anterolateral rotational laxity of the knee. However, the biomechanical effects have not been reported. Purpose: (1) To investigate the effect of ALL transection on rotational knee kinematics and (2) to determine the effect on knee biomechanics of ALL reconstruction procedures compared with lateral extra-articular tenodesis (LET). Study Design: Controlled laboratory study. Methods: A total of 12 cadaveric knee specimens were tested in the following sequence: (1) ACLintact, (2) anteromedial bundle of ACL sectioned (ACLamb ), (3) complete ACL sectioned (ACLfull ), (4) ALL sectioned (ALLsec ), (5) anatomic ALL reconstruction (ALLanat ), and (6) LET. Biomechanical anterior drawer and Lachman tests were performed in which a 90-N load was applied to the posterior tibia, and anterior translation was measured. A combined load to simulate the early phase of the pivot-shift test was executed in which a 5-N·m internal rotation moment was applied to a fully extended knee; anterior translation and internal rotation were measured. Results: Anterior translation increased across conditions for the biomechanical tests. Internal rotation during the simulated early-phase pivot-shift test was significantly different between ACLfull and ALLsec . Anatomic ALL reconstruction did not significantly reduce internal rotation or anterior translation during the simulated early-phase pivot-shift test. After LET, a significant decrease in anterior translation was found. There was no evidence of overconstraint of the knee with either anatomic ALL reconstruction or LET. Conclusion: The ALL demonstrated a role in controlling anterolateral laxity. LET had a composite effect in governing both anterior and rotational laxity. Anatomic ALL reconstruction did not reduce anterolateral rotational laxity. Clinical Relevance: Profiling the biomechanical characteristics of anterolateral reconstruction is integral to understanding the implications and potential benefit of such an additional procedure to ACL reconstruction.